Reintroducing dyssynchrony significantly increases myocardial stiffness at mitral valve closure. (3rd October 2022) - Wouters, L; Duchenne, J; Bezy, S; Papangelopoulou, K; Puvrez, A; Klop, B; Voros, G; D'hooge, J; Voigt, J U
Abstract: Background: Cardiac shear wave elastography (SWE) allows for the non-invasive assessment of myocardial stiffness via the detection of shear waves. Shear waves are mechanical waves that travel through the heart after for example mitral valve closure (MVC). The propagation speed of these waves is directly dependent on myocardial stiffness, where a higher shear wave speed correlates with a higher stiffness. However, the effect of a left bundle branch block (LBBB) and a dyssynchronous contraction pattern on shear wave speed is currently unknown. Purpose: To investigate the effect of a dyssynchronous contraction pattern caused by LBBB on shear wave speed. Methods: We included 29 non-ischemic heart failure patients with an LBBB (68±15y; 52% males) and 9 age-matched healthy volunteers (68±4y; 55% males) as controls. All LBBB patients were implanted with a CRT device and dyssynchrony was reintroduced by turning biventricular (BiV) pacing off to allow native ventricular conduction. Echocardiographic images were taken during BiV pacing on and BiV pacing off, with a conventional ultrasound machine and an experimental high frame rate ultrasound scanner. Shear waves were visualized in M-modes of the septum, colour coded for tissue acceleration. The slope of the shear waves in the M-mode represents their propagation speed. Further, longitudinal strain at MVC and the time difference between onset of septal contraction and MVC were measured (negative time values indicate that MVC occurs before onset of septal contraction). Results: There was no significant difference in shear wave speed between healthy controls and LBBB patients during BiV pacing on (4.5±1.1 m/s vs 4.9±1.2 m/s; p=0.365; Figure A). However, shear wave speed was significantly higher in LBBB patients during BiV pacing off compared to healthy controls (4.5±1.1 m/s vs 5.6±1.1 m/s; p=0.041; Figure A). Turning BiV pacing off lead to a significant increase in shear wave speed in LBBB patients (4.9±1.2 m/s vs 5.6±1.1 m/s; p=0.003; Figure A), indicating that the reintroduction of LBBB increases septal myocardial stiffness. MVC occurred significantly later after the onset of septal contraction during BiV pacing off (−9±57 ms vs 40±26 ms; p=0.001) and strain values at MVC were more negative (−0.3±0.6% vs −2.0±1.5%; p<0.001). Therefore we hypothesize that during BiV pacing off, the septal wall was further into the contraction phase at the time of MVC, leading to an increased myocardial stiffness, and thus increased shear wave speed (Figure B). Our interpretation was further strengthened by a strong correlation between the change in shear wave speed and the change in septal longitudinal strain at MVC when BiV pacing is turned off (r=0.81; p<0.001; Figure C). Conclusion: Reintroducing dyssynchrony in LBBB patients significantly increases shear wave speed at MVC. Our results suggest that the earlier contraction of the septum during dyssynchrony is an explanation for the higher septal stiffness at MVC. Funding Acknowledgement: Type of funding sources: None.